2020
DOI: 10.3389/fncel.2020.00120
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 in the Cerebrospinal Fluid Signals Disease Activity in Multiple Sclerosis

Abstract: Specific proinflammatory and anti-inflammatory molecules could represent useful cerebrospinal fluid (CSF) biomarkers to predict the clinical course of multiple sclerosis (MS). The proinflammatory molecule interleukin (IL)-6 has been investigated in the pathophysiology of MS and has been associated in previous smaller studies to increased disability and disease activity. Here, we wanted to further address IL-6 as a possible CSF biomarker of MS by investigating its detectability in a large cohort of 534 MS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 31 publications
(44 reference statements)
1
28
0
Order By: Relevance
“…Phosphorylated STAT3 (pSTAT3) was significantly higher in CD4 + T cells from relapsing-remitting MS (RRMS) patients in relapse compared with those in remission and healthy controls (HCs) ( 20 ). IL-6 level is higher in the cerebrospinal fluid (CSF) of MS patients compared with HCs ( 21 , 22 ). IL-6 receptor (IL-6R) level is significantly higher in CD4 + T cells of MS patients than HCs ( 18 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylated STAT3 (pSTAT3) was significantly higher in CD4 + T cells from relapsing-remitting MS (RRMS) patients in relapse compared with those in remission and healthy controls (HCs) ( 20 ). IL-6 level is higher in the cerebrospinal fluid (CSF) of MS patients compared with HCs ( 21 , 22 ). IL-6 receptor (IL-6R) level is significantly higher in CD4 + T cells of MS patients than HCs ( 18 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…From an inflammatory perspective, increased levels of IL-6, TNF, and IL-1β are detected in the brain, cerebrospinal fluid, and serum of patients with AD, PD, and MS, although these responses have not been yet linked to IRE1 or PERK activation (Swardfager et al, 2010;Qin et al, 2016;Chen X. et al, 2018;Stampanoni Bassi et al, 2020). Analogous to peripheral macrophages, microglia initiate inflammation upon recognition of Aβ, α-syn, and neuromelanin through TLR2 and TLR4 (Reed-Geaghan et al, 2009;Zhang et al, 2011;Kim et al, 2013).…”
Section: Potential Crosstalk Between the Upr In Immune Cells And Neuroinflammationmentioning
confidence: 99%
“…The optimal cut-off CSF IL-6 point has been found as 7.8 pg/mL for diagnosing NMO [135]. On the other hand, it has been suggested that IL-6 is a candidate for a rather non-specific prognostic biomarker as elevated levels of this cytokine are also associated with neuroinflammatory diseases other than NMO [137].…”
Section: Differences In Th17-related Markers Between Ms and Nmomentioning
confidence: 99%